Using Mindfulness to Teach Beyond Triggers - Julee Rosser (Adult Education Research Conference, 2016)
The focus of this submission is on the intersection of mindfulness education and productive dialogue for understanding gender, race, ethnicity, ability, nationality, and religion as cultural constructs that often involve triggers.
Keywords: Mindfulness Triggers Education Race Gender